Continuity and Stability of Parenting of Infants by Women at Risk for Perinatal Depression. (2nd January 2022) - Goodman, Sherryl H.; Bakeman, Roger; Milgramm, Anna
SYNOPSIS: Objective. The present study aimed to enhance understanding of continuity and stability of positive parenting of infants, across age and different settings in women with a history of depression who are at elevated risk for postpartum depression. Design. Mothers ( N = 103) with a history of major depression and their infants were observed during 5-min play and feeding interactions when their infants were 3, 6, and 12 months of age. Summary scores representing mothers' positive parenting were computed separately for each age and context based on ratings of five parenting behaviors. Mothers' depressive symptom levels were assessed at each infant age. Results. Continuity (consistency of level) and stability (consistency of rank order) were assessed across age and context at both the group and individual level. Across-age analyses revealed continuity in the play context and discontinuity in the feeding context, albeit only at the group level, as well as weak to moderate stability. Across-context analyses revealed higher positive parenting scores in play than feeding at all time points as well as weak to moderate stability. Variations in positive parenting across age and context were independent of mothers' postpartum depressive symptom levels. Conclusions. Findings based on normative samples may not generalize to women with a history of depression, who may benefit from interventions aimed at enhancing their positive parenting over the course of infancy, regardless of postpartum depressive symptom level. Results also underscore the importance of assessing parenting at multiple age points and across varying contexts.